Numa and the Nature of the Fantastic in the Fiction of Juan Benet - David K. Herzberger (Studies in 20th & 21st Century Literature, 1984)
Perhaps the most rewarding critical approach to the novels of Juan Benet is one that encompasses the irrational and seeks to reveal the mysterious— one that can be closely identified with the notion of the fantastic. The view of the fantastic developed in the present study is based on a synthetic modification of the precepts of Todorov and Rabkin, and places emphasis on the hesitation of the reader when confronted with a diametric reversal of the laws of the text. Both the literary theory and prose fiction of Benet can be closely linked to the fantastic: the former through Benet's focus on narrative uncertainty and ambiguity; the latter in a variety of important ways, but most pervasively through the character Numa. Numa recurs throughout Benet's fiction as an enigmatic and superhuman figure. He at once conforms to and transgresses the norms of the text, and inspires reader hesitation in the face of the marvelous. Through him Benet reifies many of his theoretical tenets, and also shapes the specific nature of his fantastic world.
Keywords: novel; Juan Benet; irrational; mystery; mysterious; fantastic; Todorov; Rabkin; diametric reversal; literary theory; prose fiction; ambiguity; uncertainty; marvelous